Long-term cost-effectiveness of collaborative care (vs usual care) for people with depression and comorbid diabetes or cardiovascular disease: a Markov model informed by the COINCIDE randomised controlled trial. Issue 10 (7th October 2016) - Camacho, Elizabeth M; Ntais, Dionysios; Coventry, Peter; Bower, Peter; Lovell, Karina; Chew-Graham, Carolyn; Baguley, Clare; Gask, Linda; Dickens, Chris; Davies, Linda M
Abstract : Objectives: To evaluate the long-term cost-effectiveness of collaborative care (vs usual care) for treating depression in patients with diabetes and/or coronary heart disease (CHD). Setting: 36 primary care general practices in North West England. Participants: 387 participants completed baseline assessment (collaborative care: 191; usual care: 196) and full or partial 4-month follow-up data were captured for 350 (collaborative care: 170; usual care: 180). 62% of participants were male, 14% were non-white. Participants were aged ≥18 years, listed on a Quality and Outcomes Framework register for CHD and/or type 1 or 2 diabetes mellitus, with persistent depressive symptoms. Patients with psychosis or type I/II bipolar disorder, actively suicidal, in receipt of services for substance misuse, or already in receipt of psychological therapy for depression were excluded. Intervention: Collaborative care consisted of evidence-based low-intensity psychological treatments, delivered over 3 months and case management by a practice nurse and a Psychological Well Being Practitioner. Outcome measures: As planned, the primary measure of cost-effectiveness was the incremental cost-effectiveness ratio (cost per quality-adjusted life year (QALY)). A Markov model was constructed to extrapolate the trial results from short-term to long-term (24 months). Results: The mean cost per participant of collaborative care was £317 (95% CI 284 to 350). Over 24 months, it was estimated that collaborative care was associated with greater healthcare usage costs (net cost £674 (95% CI −30 953 to 38 853)) and QALYs (net QALY gain 0.04 (95% CI −0.46 to 0.54)) than usual care, resulting in a cost per QALY gained of £16 123, and a likelihood of being cost-effective of 0.54 (willingness to pay threshold of £20 000). Conclusions: Collaborative care is a potentially cost-effective long-term treatment for depression in patients with comorbid physical and mental illness. The estimated cost per QALY gained was below the threshold recommended by English decision-makers. Further, long-term primary research is needed to address uncertainty associated with estimates of cost-effectiveness. Trial registration number: ISRCTN80309252 ; Post-results.